2018
DOI: 10.1159/000492524
|View full text |Cite
|
Sign up to set email alerts
|

Balance Control during Stance and Gait after Cochlear Implant Surgery

Abstract: Background: After cochlear implant (CI) surgery, some patients experience vertigo, dizziness and/or deficits in vestibulo-ocular reflexes. However, little is known about the effect of CI surgery on balance control. Therefore, we examined differences in stance and gait balance control before versus after CI surgery. Methods: Balance control of 30 CI patients (mean age 59, SD 15.4 years), receiving a first unilateral CI surgery, was measured preoperatively and postoperatively 1 month after the initial implant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Among all the 38 articles, after judgment based on the risk of bias analysis (JBI), analytic cross-sectional studies, and according to each study type, 25 studies showed a low risk of bias ( 9 , 14 , 16 , 24 , 27 , 31 , 33 , 35 , 36 , 38 , 39 , 42 44 , 46 , 48 55 ), 10 articles ( 15 , 23 , 25 , 26 , 28 30 , 32 , 34 , 47 ) showed a moderate risk of bias, and 3 articles ( 21 , 40 , 45 ) had a high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all the 38 articles, after judgment based on the risk of bias analysis (JBI), analytic cross-sectional studies, and according to each study type, 25 studies showed a low risk of bias ( 9 , 14 , 16 , 24 , 27 , 31 , 33 , 35 , 36 , 38 , 39 , 42 44 , 46 , 48 55 ), 10 articles ( 15 , 23 , 25 , 26 , 28 30 , 32 , 34 , 47 ) showed a moderate risk of bias, and 3 articles ( 21 , 40 , 45 ) had a high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding reports of pre-existing symptoms, the majority of articles did not mention them, however, about post symptoms, 17 cited vertigo as the main symptom ( 9 , 14 – 16 , 21 , 25 , 26 , 28 , 30 , 33 , 39 , 40 , 44 , 48 , 50 52 ), and in 5 of these ( 25 , 26 , 28 , 30 , 39 , 51 ), the round window was the surgical intervention, 5 ( 16 , 21 , 33 , 40 , 44 ) had cochleostomy, in 1 ( 25 ) both interventions were present, and the others did not mention the surgery, despite having reported the symptoms. Of all the articles eligible for this review, 44.7% ( 9 , 14 – 16 , 21 , 25 , 26 , 28 , 30 , 33 , 39 , 40 , 44 , 48 , 50 52 ) reported vertigo as a post-implantation symptom, followed by dizziness and imbalance ( 16 , 29 , 32 , 35 , 36 , 38 , 39 , 44 , 45 , 48 , 50 , 51 , 53 ); however, in 7.8% ( 34 , 54 , 55 ) of the studies, there were no reports or citations of any referred symptom ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation